Reclamation of Sodic Soil through Afforestation - Tripathi, K. P.; Singh, Bajrang (Indian Forester, 2010)
A forest ecosystem was developed on barren sodic land at Bantbra Research Station of National Botanical Research Institute, Lucknow, India during 1960s. About 74 species belonging to 34 families were recorded in this new forest, which was characterized as mixed dry sub-tropical forest with deciduous and evergreen species. The forest was classified into overstory, understory and ground layer vegetation based on the morphological variation and vertical strata of the vegetation. Frequency, density, abundance and basal area were evaluated for each species and dominants were assorted on the basis of basal area and Importance Value Index. Shannon Wiener’s diversity index measured as 3.6, 3.3, and 1.8 for overstory, understory and ground layer vegetation, respectively. Forest biomass (dry weight) was estimated to be 347 Mg ha-1 with a net primary production of25 Mg ha-1 yr-1 at the age of 40 years. Forest sequestered about 168 Mg ha-1 carbon content in their standing biomass with current accumulation rate of 11 Mg ha-1 yr-1 and conserved 8.9 TJ ha-1 energy in their standing stock. Annual energy fixation was estimated to 644 GJ ha-1. Nutrient pool and fluxes in the forest were also determined. Further, the role of litter and fine roots in reclamation of sodic soil was quantified.